THE ‘CURRICULUM OF LOVE’ AS A STRATEGIC FRAMEWORK FOR ISLAMIC EDUCATIONAL MANAGEMENT: OPTIMIZING VALUES AND INSTITUTIONAL PERFORMANCE - Abidin, Zainal (Faculty of Administrative Science, Universitas Brawijaya, 2025)
This study investigates the strategic integration of the Curriculum of Love (CoL) into Islamic educational management, focusing on its role in optimizing institutional values and performance. Employing a qualitative case study approach, data were collected from three Islamic educational institutions in East Java through in-depth interviews, non-participant observations, and document analysis. The findings reveal that successful integration of the CoL requires comprehensive policy alignment, value-oriented human resource management, organizational culture transformation, and the establishment of performance indicators that reflect moral-spiritual values alongside academic achievements. Effective managerial practices include vision-driven leadership, participatory decision-making, targeted teacher training, value-based performance appraisals, and restorative approaches to conflict resolution. The study contributes to the literature by framing the CoL not only as a pedagogical framework but also as a strategic management tool for enhancing institutional effectiveness. While the research is limited to a specific regional context, its implications offer a practical blueprint for policymakers, school leaders, and educators seeking to integrate value-based principles into educational governance.